ANALYSIS OF INTERNATIONAL CARGO TURNOVER AND CO2 EMITTED DURING ITS ORGANIZATION - Нодирбeк Курбонов (Web of Journals Publishing, 2024)
This article presents an analysis of international freight turnover and the associated CO2 emissions. It examines the key aspects affecting the efficiency and environmental consequences of freight transport, including transport routes, modes of transport and their impact on the carbon footprint.
Keywords: International Cargo Turnover, Global Trade, Logistics, Transport Corridors, Economic Integration, Transport Infrastructure, Rail Transportation, Maritime Freight Transportation, Eurasian Economic Union, TRACECA.